Decoding the Future: Genomic Sequencing’s Vital Role in Communicable Disease Prevention within Public Health Practice - A Scoping Review - Harun, Amin; Md Zamri, Ahmed Syahmi Syafiq; Zamberi, Mohd Zafrullan; Za’bah, Abi Khairul Aizad; Abd Aziz, Siti Fatimah; Mahmud, Aidalina; Abd Rahman, Anita; Ahmad Fauzi, Fatimah (IIUM Medical Journal Malaysia, 2024)
Precision public health using genomic sequencing is a new field that has gained interest from public health practitioners for prevention and control measures. This study aims to identify the various applications of genomic sequencing for the prevention of communicable diseases in public health practice. Articles containing relevant keywords were determined using a systematic search strategy applied in Medline, Scopus, and Springer electronic databases. Full text included in the study was retrieved and categorised. A total of 24 articles were included in the final review. The main themes regarding the application of genomic sequencing in the prevention of communicable disease that were found in the articles were describing transmission patterns, investigating outbreaks, diagnosing infection, developing and evaluating interventions including vaccines, outcomes response treatment, and monitoring antimicrobial resistance. In conclusion, genomic sequencing has the potential to enhance the prevention and control of communicable diseases globally.